MEDICAMENTS IN IODINE DEFICIENCY, AND THEIR CHEMICAL COMPOSITION (Scientific journal of the Fergana State University, 2023)
The article discusses the causes of iodine deficiency, the state of the spread of iodine deficiency in the world and in the Republic of Uzbekistan, synthetic and natural remedies used for its treatment are described from the information given in writing supplements, used as the “Alcoman” medicinal product, as well as methods for making tincture from it and use.